Comparison of treatment plans between IMRT with MR-linac and VMAT for lung SABR - Park, Jong Min (Radiat Oncol, 2019)
BACKGROUND: The aim of this study was to compare the plan quality of magnetic-resonance image-based intensity modulated radiation therapy (MRI-based-IMRT) with the MRIdian Linac system to that of volumetric modulated arc therapy (VMAT) with the TrueBeam STx system for lung stereotactic ablative radiotherapy (SABR). METHODS: A total of 22 patients with tumors located in the lower lobe were retrospectively selected for the study. For each patient, both the MRI-based-IMRT and VMAT plans were generated using an identical CT image set and identical structures with the exception of the planning target volume (PTV). The PTVs of the MRI-based-IMRT were generated by adding an isotropic margin of 3 mm from the gross tumor volume, whereas those of VMAT were generated by adding an isotropic margin of 5 mm from the internal target volume. For both the MRI-based-IMRT and VMAT, the prescription doses to the PTVs were 60 Gy in four fractions. RESULTS: The average PTV volume of the MRI-based-IMRT was approximately 4-times smaller than that of VMAT (p <  0.001). The maximum dose to the bronchi for the MRI-based-IMRT was smaller than that for the VMAT (20.4 Gy versus 24.2 Gy, p <  0.001). In addition, V(40Gy) of the rib for the MRI-based-IMRT was smaller than that for the VMAT (1.8 cm(3) versus 7.7 cm(3), p = 0.008). However, the maximum doses to the skin and spinal cord for the MRI-based-IMRT (33.0 Gy and 14.5 Gy, respectively) were larger than those for the VMAT (27.8 Gy and 11.0 Gy, respectively) showing p values of less than 0.02. For the ipsilateral lung, the mean dose, V(20Gy), V(10Gy), and V(5Gy) for the MRI-based-IMRT were smaller than those for the VMAT (all with p <  0.05). For the contralateral lung, V(5Gy), V(10Gy), D(1500cc), and D(1000cc) for the MRI-based-IMRT were larger than those for the VMAT (all with p <  0.05). The mean dose and V(50%) of the whole body for the MRI-based-IMRT were smaller than those for the VMAT (0.9 Gy versus 1.2 Gy, and 78.7 cm(3) versus 103.5 cm(3), respectively, all at p <  0.001). CONCLUSIONS: The MRI-based-IMRT using the MRIdian Linac system could reduce doses to bronchi, rib, ipsilateral lung, and whole body compared to VMAT for lung SABR when the tumor was located in the lower lobe.